Heat Treatment of Cast Irons - Chakrabarty I. (My University, 2025)
Cast iron is still occupying a unique position among the engineering materials because of the combination of their low cost and engineering versatility. The properties like castability, strength, machinability, hardness, wear resistance, corrosion resistance, thermal conductivity, and damping capacity are unparallel among casting alloys. Although, many of these properties are achieved in as-cast conditions, further heat treatments extend the consistency and range of properties. A wide variety of cast irons such as gray iron, malleable iron, ductile iron, and high-alloy irons are available for specific applications and these are having responses toward different types of heat treatments. Present chapter describes critically the commonly adopted heat treatments and consequent improvements in the properties for different types of cast irons. © 2017 Elsevier Inc. All rights reserved.